2015
DOI: 10.1021/jacs.5b00546
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Diboration Involving “Reductive Addition” of a Boron–Boron σ-Bond to 4,4′-Bipyridine

Abstract: A 4,4'-bipyridine-based catalyst system for diboration of pyrazine derivatives was established. The catalyst cycle consists of the following two steps: (1) reductive addition of the boron-boron bond of bis(pinacolato)diboron to 4,4'-bipyridine to form N,N'-diboryl-4,4'-bipyridinylidene and (2) oxidative boryl transfer from the intermediate to pyrazine to give N,N'-diboryl-1,4-dihydropyrazine with regeneration of 4,4'-bipyridine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 63 publications
6
48
0
2
Order By: Relevance
“…In the case of E=B and Si, a subsequent isomerization generates the corresponding 1,4‐addition product whereas addition of another equivalent of HBpin resulted in a second 1,2‐hydroboration to afford the bis‐ N ‐borylated 1,2,3,4‐tetrahydropyrazine. A similar reductive addition of 4,4′‐bipyridines has subsequently been reported using B 2 pin 2 …”
Section: Introductionsupporting
confidence: 68%
“…In the case of E=B and Si, a subsequent isomerization generates the corresponding 1,4‐addition product whereas addition of another equivalent of HBpin resulted in a second 1,2‐hydroboration to afford the bis‐ N ‐borylated 1,2,3,4‐tetrahydropyrazine. A similar reductive addition of 4,4′‐bipyridines has subsequently been reported using B 2 pin 2 …”
Section: Introductionsupporting
confidence: 68%
“…Recently, 4,4′-bipyridine (bipy) with delocalized -electrons of the pyridyl rings obtains increasing attention in preparing light emitting complexes in different technical applications, such as emitting materials for organic light emitting diodes, sensitizers in solar energy conversion, chemical sensors and so forth [6][7][8][9]. The ability of bipy to act as a rigid, rod-like organic building block in the self-assembly of coordination frameworks is well-known, such as, acting as a charge-compensating cation, a pillar bonding to inorganic skeletal backbone, an uncoordinated guest molecule and organic template, a bridge connecting two metal complex moieties, or linking a metal and an inorganic framework [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[5] Recently,t he Lewis adducts of sp 2 -sp 3 diborane compounds have been reported for the borylation or diboration of unsaturated substrates. [10] Nevertheless,t he mechanistic details of this reaction are unclear yet. In such cases,t he B-(sp 2 ) À B(sp 3 )b onds are always cleaved heterolytically.…”
mentioning
confidence: 97%
“…[5][6][7][8][9] It has been shown that diborane compounds became asource of nucleophilic boryl moiety,w hen one of the boron atoms of the diborane was tetracoordinated to as trong base (Scheme 1a). [10] Nevertheless,t he mechanistic details of this reaction are unclear yet. [6c, 7b] In addition, reductive addition of diboranes to sterically hindered pyrazines in the presence of bipyridine derivatives has also been reported.…”
mentioning
confidence: 99%